Etiological and epidemiological characteristics of infectious hemocolitis in hospitalized pediatric patients - O. I. Klimova; N. V. Gonchar; I. V. Razd’yakonova; Yu. V. Lobzin (Журнал инфектологии, 2021)
The aim of this work is to study the etiological and epidemiological features of infectious hemocolites (IG) in hospitalized children of different ages.Materials and methods of research. An analysis of the results of a survey of 3103 children admitted to hospital treatment for acute intestinal infections (AII) from January to December 2018, among which patients with IG were identified. The etiology of the disease was determined based on the results of the bacteriological method, PCR studies of faeces with Amplicens ® OKI screen-FL reagents, serological and immunological methods. Microscopic examination of faeces was performed to identify protozoa. Patients were divided into age groups: infant (n=78; 30%); early (n=74; 28,5%); preschool (n=63; 24,2%), school (n=45; 17,3%).Results. The incidence of IG in hospitalized children with AII was 8,4%. Bacterial pathogens of IG were detected in 66,5% of children, IG of unspecified etiology was diagnosed in 24,2%. Viral and bacterial infections were rarely detected (9,2%). Among intestinal viruses, rotavirus (37,5%), norovirus (29,2%) and enterovirus (20,8%) were more frequently detected in hemocolitis of combined viral and bacterial etiology. In the IG age structure, infants (30%), young children (28,5%) and pre-school children (24,2%) made up the majority. The maximum number of IG patients was detected in the summer (10,9% of all cases of AII). Salmonellosis was more often detected in autumn (31,6%), campylobacteriosis – in summer (17.9%) and autumn (24,1%), escherichiosis and shigellosis – in summer (11,5% and 6,4%, respectively). The maximum detection of IG in infants was observed in June (14,1%) and October (12,8%), in young children – in July (17,6%), in preschoolers – in June (12,7%) and November (15,9%), in schoolchildren in May (13,3% of cases) and in October (15,6%).Conclusion. The incidence of infectious hemocolites in hospitalized children with acute intestinal infections was 8,4%. The bacterial etiology of the disease was detected in 66,5% of children. The age structure of the IG was dominated by children of infant, early and preschool age. The maximum detection of patients with IG was observed in the summer.